IMPLEMENTATION OF TRIPLE BOTTOM LINE PRINCIPLES IN INFRASTRUCTURE PROJECTS IN NORTH SULAWESI - Nicolas Willem James Mandagi; Joni Kutu’Kampilong (SOSIOEDUKASI, 2025)
his study investigates integrating Triple Bottom Line (TBL) principles—social, economic, and environmental—into infrastructure planning and evaluation in North Sulawesi through a sequential mixed-methods design. First, a Cost–Benefit Analysis (CBA) estimated Net Present Value (IDR 45.2–85.4 billion), Benefit–Cost Ratio (1.1–1.8), and Internal Rate of Return (9.5 % over 30 years), confirming economic viability. Simultaneously, a Life Cycle Assessment (LCA) quantified material-related energy use and CO₂e emissions, while structured surveys and focus-group discussions captured community perceptions of benefit distribution and participation. These quantitative and qualitative insights were synthesized in a Multi-Criteria Decision Analysis (MCDA) employing the Analytic Hierarchy Process (AHP), where twelve experts assigned weights of 0.441 (social), 0.301 (environmental), and 0.258 (economic). Among three strategic alternatives, a low-emission public-private partnership scored highest (0.83) by combining robust stakeholder engagement, recycled-steel use with offset mechanisms, and strong long-term returns; sensitivity analysis (±10 % environmental weight) confirmed its ranking stability. By mapping outcomes to SDG 9 (Industry, Innovation and Infrastructure), SDG 11 (Sustainable Cities and Communities), SDG 12 (Responsible Consumption and Production), and SDG 13 (Climate Action), the study demonstrates that a TBL-based framework can simultaneously secure financial performance, advance social equity, and reduce environmental impact. Recommendations include formalizing hybrid financing, enhancing participatory platforms, and incentivizing low-carbon materials.